A Critical Review of the Dominance of Algorithms in the Formation of Students' Social Realities in the Modern Era - Puput Tri Anggara; Lutfi Bangun Lestari (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Jurai Siwo Lampung, 2026)
The development of digital technology has transformed social experiences, interactions, and the distribution of knowledge, with algorithms acting as mechanisms of power that shape perceptions, behaviours, and social meanings. Algorithms are not merely technical tools, but rather mediators of experience that influence how humans understand the world, as emphasized by Heidegger as a mode of revealing and Don Ihde as a mediator of experience. Normatively, Amartya Sen emphasizes the importance of individual critical capabilities to assess and negotiate the influence of algorithms for the sake of freedom and justice. This study uses a synthesis of scientific literature to examine the dominance of algorithms and their implications for freedom, human values, and education. The results of the study indicate that the dominance of algorithms has the potential to limit individual freedom by narrowing information choices, eroding human values ​​through dehumanization in digital interactions, and demanding educational transformation in the form of strengthening critical and reflective digital literacy. Therefore, education needs to foster intellectual autonomy, ethical awareness, and evaluative abilities so that individuals can actively participate in the digital ecosystem dominated by algorithms, rather than simply being passive consumers of information.